PENGARUH STRATEGI KEUNGGULAN BERSAING DAN STRATEGI PEMASARAN TERHADAP PENJUALAN MANGGA HARUMANIS (Mangifera indica L): (Suatu Kasus Pada Pedagang Mangga Harumanis di Kecamatan Tempuran, Kabupaten Karawang, Provinsi Jawa Barat) - Juhana (OrchidAgri, 2025)
This study aims to analyze the Influence of Competitive Excellence Strategy and Marketing Strategy on the Sales of Harumanis Mango The respondent determination technique was carried out by census of 75 units of Harumanis mango traders. The analysis technique used is SEM (Structural Equetion Modelling). The results of the research obtained the Competitiveness Strategy Achievement of 82,95 % of the very good criteria. Marketing Strategy achieved 73,85% and Harumanis Mango Sales achieved 75.25%. The strongest Competitive Advantage Strategy Formation Dimension is Product Differentiation, The strongest Marketing Strategy Forming Dimension is Partertship and the strongest mango harumanis Sales Forming Dimension is the Transaction Process. There is a positive correlation between the Competitive Advantage Strategy and the Marketing Strategy which is shown by the correlation coefficient number r12 = 0.97, which can be interpreted as the better the Competitive Advantage Strategy. then the Marketing Strategy will be better, and vice versa. The Competitive Advantage Strategy and Marketing Strategy had a positive effect on the Sales of Harumanis Mango with a contribution of 33.78% and 23.14%, respectively. It is recommended that sellers can maintain a good relationship with customers even better. Communication with mobile phones needs to continue to be built and offer products, especially when new products come with attractive and quality performance. It is recommended that the mango packaging should be made more attractive and include thanks and prayers for buyers.